From newsletters to an Australasian journal and beyond - Millett, Stephan (Routledge, 2018)
This chapter charts the beginnings of the official journal of the Federation of Australasian Philosophy in Schools Associations (FAPSA), from the early news letters of the Philosophy for Children (P4C) movement in Australia, through to the launch of Critical & Creative Thinking (C&CT) in 1993 and the difficulties of keeping the journal alive until its demise in 2009. It then records the resurrection of FAPSA's journal as a peer-reviewed, online open-access journal under a new name in 2014. It is also a story of the people whose commitment during nearly three decades contributed to one of the most important parts of the Australian story of philosophy with children. The journal in its various forms was committed to the theoretical and pedagogical exploration of teaching philosophy to school-aged children, but like many journals it struggled in a publishing climate that included a proliferation of journals, difficulty in funding publication costs, and the changing nature of academic publishing, including the rise of online publishing and changes to the rules by which the quality of academics' output are judged.